DOI: 10.21007/etd.cghs.2016.0406
|View full text |Cite
|
Sign up to set email alerts
|

Mild Traumatic Brain Injury with Associated Visual System Dysfunction: Investigating Histopathology, Functional Correlates, and a Novel Therapeutic Immune Modulator

Abstract: Arguably the most important recognitions are due to my parents Michael and Sally, and my siblings Jessica, Lara, and Michael. You helped mold me into the person I am, and have provided unwavering support and assistance through my entire journey. No words can convey my gratitude. Also to my beautiful and intelligent daughter Elowyn, you are too young to read this now but you have brought me joy and grounded me through some of the toughest days. You have also frustrated me to tears, a feat your grandfather would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 323 publications
(393 reference statements)
0
4
0
Order By: Relevance
“…Several studies have reported thinning of the retina in response to blast injury 53,54 ; yet, other studies have also reported thickening. 55,56 The severity of the blast overpressure conditions employed may contribute to these differences.…”
Section: Persistence Of Gliotic Response Several Months After Blast Ementioning
confidence: 99%
“…Several studies have reported thinning of the retina in response to blast injury 53,54 ; yet, other studies have also reported thickening. 55,56 The severity of the blast overpressure conditions employed may contribute to these differences.…”
Section: Persistence Of Gliotic Response Several Months After Blast Ementioning
confidence: 99%
“…This response was observed in their model as regions of microglial cell activation throughout areas of the brain important for visual processing. 25 Yet another study concluded that TBI of any form can cause cognitive, behavioral and immunologic changes in later life, which underscores the problem of underdiagnosis of mild TBI that can cause long-term neurological deficits. TBI disrupts the blood -brain barrier (BBB) leading to infiltration of immune cells into the brain and subsequent inflammation and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 4 ] Traumatic brain injury disrupts the blood–brain barrier, leading to the infiltration of immune cells into the brain and subsequent inflammation and neurodegeneration or disruption of neural networks, thus resulting in the manifestation of symptoms. [ 5 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Traumatic brain injury disrupts the blood-brain barrier, leading to the infiltration of immune cells into the brain and subsequent inflammation and neurodegeneration or disruption of neural networks, thus resulting in the manifestation of symptoms. [5,6] The most common visual deficits associated with mTBI include oculomotor dysfunction (accommodative, version, and vergence) and their associated reading problems, photosensitivity, and visual field defects. [4,7,8] Visual photosensitivity is an abnormal intolerance to light.…”
Section: Introductionmentioning
confidence: 99%